Valoração aduaneira e preços de transferência: pontos de conexão e distinções sistêmico-aplicativas - Vita, Jonathan Barros (2010)
Firstly, it shall be explicated that the scientific approach of this work has as premises the coupling between Linguistics Theory and System s Theory. This essay is divided into three parts, each one with its own chapters, which can be divided into: the theoretical instruments as starting point; the instruments and structures which have pertinence with this work thru a research into national and comparative law texts; and the clearing of the studied legal institutes with its specificities and connecting points. The first part deals with the fundaments of Legal Logics and Linguistics Theory adopted and its counterweights and complements in System s Theory, resulting in the third chapter which is the consolidation of the theoretical support used in this work. Second part defines the institutes of Brazilian law, specially, using the Matrix Rule of Tax Incidence, focusing into the manifestation of the word tax and into the taxable basis. Also, there is a chapter dedicated to the problems of the international law coupled to the problems deriving from the integration with the internal law, specially, with tax law. Last Part, with three chapters, was meant to define and demonstrate the application of each one of the studied institutes, which are: customs valuation and transfer pricing. Final chapter deals with the interaction between these two institutes in their structures, functions and relationships, pointing out convergences and perspectives